ADAM17 Mediates Hypoxia-Induced Keratinocyte Migration via the p38/MAPK Pathway. (28th October 2021) - Zhu, Guoqin; Liu, Jie; Wang, Yuan; Jia, Naixin; Wang, Weiyi; Zhang, Junhui; Liang, Yi; Tian, Hao; Zhang, Jiaping
Abstract : Although hypoxia has been shown to promote keratinocyte migration and reepithelialization, the underlying molecular mechanisms remain largely unknown. ADAM17, a member of the metalloproteinase superfamily, has been implicated in a variety of cellular behaviors such as proliferation, adhesion, and migration. ADAM17 is known to promote cancer cell migration under hypoxia, and whether or how ADAM17 plays a role in hypoxia-induced keratinocyte migration has not been identified. Here, we found that ADAM17 expression and activity were significantly promoted in keratinocytes under hypoxic condition, inhibition of ADAM17 by TAPI-2, or silencing of ADAM17 using small interfering RNA which suppressed the hypoxia-induced migration of keratinocytes significantly, indicating a pivotal role for ADAM17 in keratinocyte migration. Further, we showed that p38/MAPK was activated by hypoxia. SB203580, an inhibitor of p38/MAPK, significantly attenuated the upregulation of ADAM17 as well as the migration of keratinocytes induced by hypoxia. Activation of p38/MAPK by MKK6 (Glu) overexpression, however, had adverse effects. Taken together, our study demonstrated that hypoxia-induced keratinocyte migration requires the p38/MAPK-ADAM17 signal axis, which sheds new light on the regulatory mechanisms of keratinocyte migration. Our study might also help in developing therapeutic strategies to facilitate wound healing in vivo, where cells are migrated in a hypoxic microenvironment.